-1-5x=-36

Simple and best practice solution for -1-5x=-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1-5x=-36 equation:


Simplifying
-1 + -5x = -36

Solving
-1 + -5x = -36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + -5x = -36 + 1

Combine like terms: -1 + 1 = 0
0 + -5x = -36 + 1
-5x = -36 + 1

Combine like terms: -36 + 1 = -35
-5x = -35

Divide each side by '-5'.
x = 7

Simplifying
x = 7

See similar equations:

| Z+5=8 | | 20-13=20+9x | | 1.3+0.5x=-3.14 | | 8^2+9(12/3*2)-7 | | 16/8=n/36 | | (3)(2)/2-4 | | -6x+1=7-6x | | 153/24 | | 9(v+1)-3v=2(3v+1)-5 | | 1.3c=3c+2.8 | | B-8+6b=24 | | 3(x-3)=6x-18/2 | | 5(2.4-4)=8 | | 568-507x=567 | | 4(-15)=13-6(4) | | -7(7x+6)-3(x-9)= | | 7=-5+6(-8x+2) | | -11=3x+7-3x | | 5y-11-2y^9=0 | | 25x-3=35x+3 | | 7x+9+3y+4=143 | | 5x+39=3 | | 6x=4(5+x) | | 0=2x^2-8x+3 | | -4(4+a)= | | m+14=-3 | | 5(3+6x)-2=163 | | (a+2)/(2)=-1 | | 10+6q=14+5q | | 37-6x=61-2x | | -3(6y-7)-y=-3(y-2) | | 5x^9*2u*2u^2x^9= |

Equations solver categories